Perangkat Media Terapi Bagi Anak Penderita Fobia Jarum Suntik (Trypanophobia) Menggunakan Teknologi Augmented Reality - Evans Fuad; Rahmad Gunawan; Januar Al Amien; Ulva Elviani (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2019)
Phobia is a condition in which a person experiences excessive fear of a particular object, giving rise to irrational fears that can threaten personal safety. Based on the data obtained from the Siak District Health Office in conducting immunizations at SDN 003 Benteng Hilir, out of 25 class 1 (one) elementary school students who were immunized, 18 of them suffered from needle phobia (Trypanophobia). Therefore, to overcome this problem, it is necessary to build an application as a medium for the therapy of needle phobia. The application that will be built in this study applies augmented reality technology as a mobile-based therapeutic medium. The approach used is systematic desentisiasi to the stage of flooding, where the medical team will guide patients in conducting therapy which begins with providing information about phobias through the application then directs the mobile to the marker bracelet that has been installed in the patient's hand so that the patient can interact with the syringe object directly. Based on the results of tests conducted in blackbox, it can be concluded that the application of trypanophobia can provide sufficiently clear information to patients and can help the medical team quickly control the patient's fear before injection